2020
DOI: 10.5114/aoms.2020.94495
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of inflammatory markers, disease severity and comorbidities in very elderly patients with acute respiratory diseases

Abstract: IntroductionThe study aimed to evaluate the potential role of inflammatory markers (neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), platelet to mean platelet volume (PLT/MPV), C-reactive protein (CRP), CRP/albumin) and demographic, clinical and laboratory parameters in predicting mortality in elderly patients.Material and methodsA total of 1971 very elderly (age ≥ 80 years) patients hospitalized due to acute respiratory diseases were included in this retrospective cohort study. Data o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…A previous study reported that CAR was superior to NLR in the prediction of mortality, but another study reported that NLR was superior to CAR in geriatric patients. 13,14 According to our results, CAR and NLR had similar predictive value. Both variables are useful for predicting mortality.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…A previous study reported that CAR was superior to NLR in the prediction of mortality, but another study reported that NLR was superior to CAR in geriatric patients. 13,14 According to our results, CAR and NLR had similar predictive value. Both variables are useful for predicting mortality.…”
Section: Discussionsupporting
confidence: 66%
“…4,9,11,12 Two previous studies reported NLRs for predicting inhospital mortality among elderly patients of 7.1 and 7.7, respectively. 13,14 NLR was significantly higher in patients who died than in those who survived in this study (P < 0.001). NLR of !4.02 was associated with increased mortality.…”
Section: Discussionmentioning
confidence: 49%
“…According to published literature, several PM-related mechanistic actions leading to increased vulnerability to SARS-CoV-2 may be proposed, including: 1) dysregulation of early-phase immune response leading to reduced immune defences [10,17]; 2) inflammation and injury of airways [18,31]; 3) exacerbation of pre-existing disorders (e.g. chronic obstructive pulmonary disease, asthma, cardiovascular diseases, etc.)…”
Section: Discussionmentioning
confidence: 99%